Arthritis autoantibodies in individuals without rheumatoid arthritis: follow-up data from a Dutch population-based cohort (Lifelines). (28th June 2020) - Westra, Johanna; Brouwer, Elisabeth; Raveling-Eelsing, Elisabeth; Arends, Suzanne; Eman Abdulle, Amaal; Roozendaal, Caroline; van Delft, Myrthe A M; Toes, Rene E M; Trouw, Leendert A; Vissink, Arjan; de Smit, Menke J
Abstract: Objectives: To assess whether the presence of arthritis autoantibodies alongside IgG ACPA predicts clinically suspect arthralgia in ACPA-positive subjects without RA. Methods: In the population-based Lifelines cohort ( n  = 40 136), 308 IgG ACPA-positive individuals without RA were present. Serum levels of IgA ACPA, IgA and IgM RF, and IgG anti-carbamylated antibodies were measured at baseline. Individuals were divided based on the Connective tissue disease Screening Questionnaire after 2 years follow-up. Antibodies to Porphyromonas gingivalis were determined at baseline and related to presence of periodontitis and joint complaints at 2 years follow-up. Results: Of 308 subjects 53.6% were also seropositive for IgA ACPA, 42.2% for IgM RF, 23.7% for IgA RF and 13.6% for anti-carbamylated antibodies. We defined 75 persons with clinically suspect arthralgia at risk for RA based on CTD Screening Questionnaire at follow-up. Significantly more seropositivity for IgM RF and higher levels of IgG ACPA, IgA ACPA and IgM RF were found in clinically suspect arthralgia compared with no-clinically suspect arthralgia. In multivariate logistic regression correcting for age, gender and never smoking, positivity for three or more extra autoantibodies was significantly associated with clinically suspect arthralgia. Although levels of anti- P. gingivalis were not different between groups, they were significantly correlated to levels of both RFs, and both ACPAs in clinically suspect arthralgia. Conclusions: ACPA-positive individuals without RA who develop clinically suspect arthralgia have more and higher levels of other arthritis autoantibodies at baseline. Levels of anti- P. gingivalis are not related to self-reported periodontitis or clinically suspect arthralgia, but are correlated to arthritis autoantibodies in clinically suspect arthralgia.